Access to AgriculturalInputs, Technology and Information, Communicating with Farmers,and the Role of Women in Agriculture: Perceptions of Iraqi Extension Agents - Rita Abi-Ghanem; Lynne Carpenter-Boggs; Richard T Koenig; Jeffrey L Ullman; Kevin M Murphy; Chris Pannkuk (Journal of International Agricultural and Extension Education, 2013)
The goal of this study was to gain a more comprehensive understanding ofaccess to inputs,technology and information available toIraqi extension agents,and to ascertain current farmercommunication strategies and gender roles within the diverse Iraq agricultural extension system.The conflicts, government policies, and economic sanctions that have enveloped Iraq over thelast several decades have significantly impacted access to agricultural resources. Iraqi extensionpersonnel participating inthe Iraq AgriculturalExtension Revitalization (IAER)programprovided their perspective on the availability of agricultural supplies, technology and relatedinformation. About two-thirds of the extension agents indicated that the flow and availability ofagricultural supplies has become less restricted and generally felt that there was greater accessto basic agricultural information compared to the previous decade. Despite perceivingnoticeable improvement overall in access to agricultural supplies and technology, over 83% ofthe program attendees agreed that access to agricultural inputs was currently insufficient tosuccessfully promote productive agricultural practices. An overwhelming preference for face-to-face communication by both farmers and extension personnel also limits the extent to whichagricultural information can be disseminated. In addition, several regional and gender-baseddifferences emerged.Notably, it appears that farmers donot approachfemaleextensionpersonnel equally, wherein better educated farmers are more likely to interact with femaleextensionagents.We suggest that an approach based on a horizontal exchange of knowledgebetween extension personnel and local farmers, coupled with a better integration of womenextension personnel, will help a revitalized Iraqi extension system achieve greater agriculturalsustainability
Keywords: Iraq; InternationalAgriculturalExtension; ResourceAvailability; SustainableAgriculture; Gender Issues